Исследование адсорбции 99mTc на магнитоуправляемых наноколлоидах Fe@C (IDA); Известия вузов. Физика; Т. 53, № 10-2 - Постников П. С. Павел Сергеевич; Скуридин В. С. Виктор Сергеевич; Рогов А. С. Александр Сергеевич; Филимонов В. Д. Виктор Дмитриевич; Нестеров Е. А. Евгений Александрович; Трусова М. Е. Марина Евгеньевна; Садкин В. Л. Владимир Леонидович; Нестерова Ю. В. Юлия Владимировна (2010, 2010)
Заглавие с экрана